RNA helicase YTHDC2 promotes cancer metastasis via the enhancement of the efficiency by which HIF-1α mRNA is translated. Issue 1 (28th June 2016) - Tanabe, Atsushi; Tanikawa, Kenya; Tsunetomi, Mai; Takai, Kaori; Ikeda, Hiroto; Konno, Junpei; Torigoe, Toshihiko; Maeda, Hideki; Kutomi, Goro; Okita, Kenji; Mori, Mitsuru; Sahara, Hiroeki
Abstract: YTH domain containing 2 (YTHDC2) is a member of the DExD/H-box family of ATP-dependent RNA helicases. We previously found that YTHDC2 expression is up-regulated in several human cancer cells. In this study, we demonstrate novel roles for YTHDC2 in metastasis of colon tumor cells via translation-dependent pathway. Knockdown of YTHDC2 attenuated protein expression of metastasis-related genes, such as hypoxia-inducible factor-1alpha (HIF-1α), and inhibited metastasis of colon tumor cells in vitro and in vivo. To confirm that YTHDC2 promotes translation initiation by unwinding the 5′-untranslated region (5′UTR) of mRNA, we constructed a firefly luciferase reporter containing the 5′UTR of the HIF-1α mRNA and showed reduction in luciferase activity in YTHDC2-silenced cells. Furthermore, we examined expression levels of YTHDC2 by immunohistochemical staining in human colon cancer tissues from 72 patients and found a significantly positive correlation between YTHDC2 expression and the tumor stage, including metastasis. In conclusion, these results suggest that the RNA helicase YTHDC2 contributes to colon tumor metastasis by promoting translation of HIF-1α and that YTHDC2 is potentially a diagnostic marker and target gene for treating colon cancer patients.